Experimental method for curing superconducting coil by using zirconium tungstate filled epoxy resin capable of resisting thermal mismatch

By using zirconium tungstate/epoxy resin composite material and wet winding method technology, the thermal mismatch stress problem of superconducting coils in low temperature environments is solved, the mechanical properties and stability of the coil are improved, and the operation is simplified, and suitable for high temperatures is suitable for and cryogenic superconducting applications.

CN119207996AActive Publication Date: 2024-12-27LANZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411375058.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Traditional superconducting coils cause radial tensile stress caused by differences in thermal expansion coefficients in low temperature environments to cause cracks and critical current degradation of superconducting layer. Although the existing technology reduces the risk of interface cracking, it does not fundamentally solve the thermal mismatch stress and has a stable structure. The properties are reduced, causing problems such as interface friction and boundary warping.

Method used

The impregnated coil is wound with low thermal expansion coefficient and high mechanical strength zirconium tungstate/epoxy resin composite material. Through wet winding and vacuum defoaming treatment, the thermal expansion coefficient of the coil is reduced and the mechanical properties are improved, radial stress is reduced, and the Application range of coils.

Benefits of technology

It effectively reduces the risk of thermal mismatch stress of superconducting coils, improves structural stability, enhances the mechanical properties of the coils, reduces the risk of failure, and simplifies the operating process, suitable for high- and low-temperature superconducting applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119207996A_ABST
    Figure CN119207996A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of superconducting tape testing, and relates to an experimental method for curing a superconducting coil by using zirconium tungstate filled epoxy resin for resisting thermal mismatch. A traditional method has the problem that thermal expansion coefficients of epoxy resin and a superconducting tape are not matched, so that an epoxy impregnated superconducting coil is easily layered and damaged, and even the structure of the superconducting coil is damaged. By preparing the zirconium tungstate / epoxy resin composite impregnating material with a low thermal expansion coefficient, a brand-new scheme is provided from the root cause of thermal mismatch of the impregnating material and the superconducting material, the thermal expansion coefficient of epoxy resin is reduced, and the thermal expansion coefficient of the superconducting material is reduced. Therefore, the risk of interface cracking and failure of the impregnated superconducting coil caused by thermal mismatch stress is reduced; the thermal expansion coefficient of the impregnated material is reduced, mechanical properties are considered, it is guaranteed that the impregnated coil has high mechanical strength, and the failure risk is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of superconducting tape testing, and in particular relates to an experimental method for a zirconium tungstate-filled epoxy resin-cured superconducting coil capable of resisting thermal mismatch. Background Art

[0002] Due to the significant difference in thermal expansion coefficients between traditional epoxy impregnation materials and superconducting tapes, radial tensile stress accumulates during the cooling process of the coil from room temperature to a low-temperature operating environment (such as liquid nitrogen, 77K). Once the radial tensile stress exceeds the interface strength of the superconducting tape, delamination failure will occur, resulting in cracks in the superconducting layer, causing significant irreversible degradation of the superconducting critical current, and even causing coil failure.

[0003] In order to prevent the delamination failure of high-temperature superconducting tapes in epoxy impregnated coils, Yanagisawa et al. developed a polyimide coating manufacturing technology, and the delamination failure can be replaced by the debonding between polyimide and epoxy resin. Similarly, Mizuno et al. proposed an epoxy impregnated coil technology in which high-temperature superconducting tapes and polytetrafluoroethylene (PTFE) tapes are co-wound, in which the polytetrafluoroethylene tape effectively prevents the mechanical degradation of the coil due to interface cracking. In addition, Yin et al. proposed a method of coating high-temperature superconducting tapes with a release agent to reduce delamination failure. The basic idea of ​​the above methods is to use other interface cracks to replace the cracks inside the superconducting tape. Although the failure risk caused by interface cracks can be reduced, the thermal mismatch stress is not fundamentally reduced. In addition, the cracks on other interfaces reduce the constraints between coil layers, reduce the structural stability, and cause problems such as interface friction and boundary warping, which further lead to the failure and damage of the superconducting coil. Summary of the invention

[0004] In order to solve the problems raised in the background technology, the present invention provides an experimental method for a zirconium tungstate-filled epoxy resin-cured superconducting coil that resists thermal mismatch. The zirconium tungstate / epoxy resin composite impregnation material with low thermal expansion coefficient and high mechanical strength is used for coil winding to achieve an epoxy impregnated coil that resists thermal mismatch, reduces the risk of structural failure, is easy to operate, and is economical and efficient.

[0005] To this end, the present invention adopts the following technical methods: An experimental method for a thermally mismatch-resistant zirconium tungstate-filled epoxy resin-cured superconducting coil comprises the following steps: 1) Preparation of superconducting tape: Select the superconducting tape required for the experiment, and weld the current leads at both ends of the superconducting tape; arrange voltage welding points at a specified interval along the length direction of the superconducting tape, and weld silver tape leads to each voltage welding point; 2) Preparation of impregnation materials: Use Stycast@2850FT epoxy resin material and Catalyst 24LV curing agent to prepare epoxy resin matrix; the doped filler is zirconium tungstate ZrW2O8 powder with a particle size of 1μm and a purity greater than 99%; Mix epoxy resin and curing agent in proportion, stir well, add zirconium tungstate powder, stir well; use vacuum pump for vacuum degassing; 3) Coil winding: fix the winding reel of the superconducting tape prepared in step 1) on the pay-off wheel, fix the coil frame tooling on the winding machine, and use the wet winding method to impregnate the coil; Lead the superconducting tape in the winding reel to the coil frame tooling and glue and fix the superconducting tape; evenly apply the impregnation material prepared in step 2) to the upper and lower surfaces of the superconducting tape, and at the same time start the winding machine to start winding the coil while applying the impregnation material; during the winding process, pay attention to the silver tapes not being able to fit together and use the impregnation material to separate them.

[0006] After the winding is completed, it is subjected to constant temperature curing to obtain the required superconducting coil.

[0007] Furthermore, in the step 1), the superconducting tape is provided with voltage welding points at the 1st turn, the 6th turn, the 16th turn, the 26th turn, and so on, with a voltage welding point being provided every 10 turns.

[0008] Furthermore, in step 1), the current lead is a silver tape with a thickness of 0.1 mm, a width of 3 mm, and a length of about 10 cm; the specifications of the silver tape on each voltage welding point are a thickness of 0.1 mm, a width of 3 mm, and a length of about 3 cm.

[0009] Furthermore, in the step 2), the epoxy resin material and the curing agent are mixed in a mass ratio of 100:7-10.

[0010] Furthermore, in step 2, the added mass of the zirconium tungstate powder accounts for 9% to 11% of the sum of the mass of the epoxy resin material and the curing agent.

[0011] Furthermore, in the step 3), the curing is carried out in a drying oven at a constant temperature of 25° C. for 24 hours.

[0012] The beneficial effects of the present invention are: 1. Based on the fundamental cause of thermal mismatch between the impregnating material and the superconducting material, the present invention proposes a new solution to reduce the thermal expansion coefficient of the epoxy resin, thereby reducing the risk of interface cracking failure of the impregnated superconducting coil due to thermal mismatch stress; 2. Reduce the thermal expansion coefficient of the impregnated material while taking into account the mechanical properties, ensuring that the impregnated coil has high mechanical strength and greatly reducing the risk of failure; 3. The selected doping material, zirconium tungstate, has a wide negative thermal expansion temperature range (2~1443K), covering the application temperature of high-temperature superconductivity and low-temperature superconductivity; 4. Reduce the radial stress of the coil by improving the impregnation material, wind more turns of the insulating impregnated coil at a smaller radius, and expand the application range of the coil; 5. Different from the prior art which usually introduces a weak interface between the epoxy resin and the superconducting tape to protect the superconducting tape from delamination by the weak interface failure, but the structural stability is destroyed, this method directly reduces the thermal expansion coefficient of the impregnated material; 6. Different from the vacuum pressure impregnation method commonly used in the prior art, the improved impregnation material has a higher viscosity, and the wet winding method can be used to impregnate the coil, which is simpler and faster to operate and is more suitable for winding small coils. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a preparation flow chart of the zirconium tungstate / epoxy resin composite material of the present invention; Figure 2 It is a schematic diagram of the positions of the current leads and voltage leads; Figure 3 It is a schematic diagram of the coil winding process; Figure 4 It is a schematic diagram of the impregnated coil structure; Figure 5 is the thermal expansion coefficient of four different ratios of zirconium tungstate / epoxy resin composites; Figure 6 It is the maximum tensile strength curve of zirconium tungstate / epoxy resin composite materials with different proportions at room temperature; Figure 7 It is the maximum tensile strength curve of zirconium tungstate / epoxy resin composite materials with different proportions at 77K; Figure 8 It is the maximum shear strength curve of zirconium tungstate / epoxy resin composite materials with different proportions at room temperature; Fig. 9 It is the maximum shear strength curve of zirconium tungstate / epoxy resin composite materials with different proportions at 77K; Fig.10 It is a structural schematic diagram of the coil skeleton tooling. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments: Superconducting tape preparation: (1) A 95 μm thick, 4 mm wide REBCO tape produced by Shanghai Superconducting Technology Co., Ltd. was used.

[0015] (2) Calculate the amount of wire required according to the required number of turns and wind the strip onto the winding reel.

[0016] (3) Use solder to solder a silver strip with a thickness of 0.1 mm, a width of 3 mm, and a length of about 10 cm at the beginning and end of the strip as a current lead.

[0017] (4) Starting from the innermost turn, place voltage welding points in the 1st turn, the 6th turn, the 16th turn, the 26th turn, and so on. Place a voltage welding point every 10 turns. Use a silver ribbon with a thickness of 0.1 mm, a width of 3 mm, and a length of about 3 cm to lead out, and then solder the polished enameled wire at both ends to the silver ribbon.

[0018] Be careful to make the solder as thin as possible to prevent the current and voltage soldering points from protruding and damaging the superconducting tape.

[0019] Pay attention to measuring the passages at both ends of the enameled wire.

[0020] Be sure to wear gloves during operation to avoid contact between your hands and the strip.

[0021] If the operating environment is high in humidity, both the original superconducting tape and the prepared tape winding reels should be stored in a drying cabinet.

[0022] Preparation of impregnation materials: (1) Stycast@2850FT epoxy encapsulation material and Catalyst 24LV curing agent were used to prepare the epoxy matrix. Zirconium tungstate (ZrW2O8) powder with a particle size of about 1 μm and a purity of more than 99% was selected as the doping filler.

[0023] (2) First, Stycast @ Mix 2850FT epoxy resin and Catalyst 24LV curing agent in a mass ratio of 100:8 and stir thoroughly.

[0024] (3) Add 10% (±0.5%) mass fraction of zirconium tungstate powder to the epoxy resin and stir thoroughly.

[0025] (4) Use a vacuum pump to perform vacuum degassing on the evenly mixed sample.

[0026] Be sure to start winding the coil immediately after preparing the impregnation material.

[0027] Coil Winding Steps: (1) The coil prestress is planned to be 10MPa.

[0028] (2) The coil is impregnated using the wet winding method.

[0029] (3) Fix the winding reel with the prepared strip on the pay-off wheel.

[0030] (4) Fix the coil frame tooling to the winding machine.

[0031] (5) Gently guide the prepared strip from the winding reel to the coil frame tooling and fix the head end with Kapton tape.

[0032] (6) Gently straighten the strip between the winding drum and the coil frame tooling so that tension can be applied to the strip when winding begins.

[0033] (7) Use a disposable brush to evenly brush the prepared zirconium tungstate filled epoxy resin impregnated material on the upper and lower surfaces of the strip, and at the same time start the winding machine and wind it at a speed of 4 turns / min.

[0034] (8) After winding the tape, tape the end with Kapton tape, cut the remaining tape, and gently wrap the outermost turn of the coil a few times with Kapton tape without adding tension.

[0035] During the winding process, please note that the silver tapes cannot be stuck together and can be separated by impregnating materials.

[0036] Note that the impregnation material may be slightly more than the expected thickness when brushing, as the excess impregnation material will overflow under the action of tension.

[0037] Note the cardboard at the bottom to prevent epoxy from dripping onto the ground and being difficult to clean.

[0038] (12) After winding, place it in a drying oven at a constant temperature of 25°C to cure for 24 hours.

[0039] Example 1 Experimental conditions: 4K-285K, ultra-low temperature-electric-magnetic multi-field superconducting material mechanical properties testing equipment of the Superconducting Mechanics Laboratory of Lanzhou University Experimental steps: (1) Stycast @ 2850FT epoxy resin and Catalyst 24LV curing agent were mixed in a mass ratio of 100:8; (2) According to the designed formula, zirconium tungstate powder with mass fractions of 0, 10%, 20%, and 30% was added to the epoxy resin respectively; (3) Stir the sample thoroughly and mix well; (4) Use a vacuum pump to perform vacuum degassing on the evenly mixed sample; (5) injecting it into the prepared silicone mold; (6) Place in a constant temperature box and cure at 25°C for 24 hours; (7) Connect the strain gauges of the test sample and the compensation element to the sensor in a half-bridge manner according to the Wheatstone bridge connection method; (8) During the test, the temperature was first lowered to 4K, then the refrigerator was turned off and the temperature was naturally restored to 285K. During the restoration process, the strain relative to 4K was recorded every 10 seconds. (9) The thermal expansion coefficients of composite epoxy materials with different zirconium tungstate doping concentrations at 4-285K were obtained by the difference-differentiation method.

[0040] Experimental results: Figure 5 The thermal expansion coefficient results of composite epoxy materials with different mass fractions of zirconium tungstate doping concentrations at 4-285K obtained by experimental measurement are shown. It can be seen that the addition of zirconium tungstate effectively reduces the thermal strain of the composite material under large temperature changes. As the mass fraction of zirconium tungstate powder in the composite material gradually increases, the thermal expansion coefficient of the composite material shows a significant downward trend.

[0041] Example 2 Experimental conditions: Room temperature, 77K; tensile performance test is carried out according to ASTM D638, using type IV sample size, and the test speed is 0.2 mm / min. Shear strength test is carried out according to GB / T 7124-2008 adhesive test standard, and the test speed is 0.2 mm / min.

[0042] Experimental steps: (1) preparing four tensile specimens and shear specimens of zirconium tungstate / epoxy resin composite materials with different ratios in Example 1; (2) Clamp the sample in the tensile machine and set the tensile plan; (3) Stretch the sample until it breaks and record the stress and strain; (4) Process the data to obtain the tensile stress-displacement curve and the shear stress-displacement curve.

[0043] Experimental results: The tensile strength and shear strength tests were carried out on four composite materials with different ratios, such as Figure 6 and 7 As shown in the figure, the test results at room temperature and 77K show that the mechanical strength first increases and then decreases with the increase of ZrW2O8 content, among which the 10wt.% ZrW2O8 sample exhibits the best mechanical properties: the maximum tensile strength at room temperature is increased by 11.62% compared with pure epoxy resin, and the shear strength is increased by 7.0%; at a low temperature of 77K, the maximum tensile strength is increased by 12.67% compared with pure epoxy resin, and the shear strength is increased by 5.86%.

[0044] Example 3 Experimental conditions: Simulation Parameters Usage Figure 5 The thermal expansion coefficients of pure epoxy resin and 10wt.% zirconium tungstate / epoxy resin composite materials were measured. The number of coil turns was 150, the epoxy between turns was 80μm, and the inner radius of the coil was 8mm and 6mm, respectively.

[0045] Experimental steps: Simulate the radial stress of the coil when the coil is lowered from room temperature to liquid nitrogen environment.

[0046] Experimental results: There is a clear contrast in radial stress between the pure epoxy resin impregnated coil and the 10wt.% zirconium tungstate / epoxy resin composite material impregnated coil. The radial stress of the improved impregnated coil with inner radius r=8mm is only 4.18% of that of the pure epoxy coil, and the radial stress of the improved impregnated coil with inner radius r=6mm is only 4.31% of that of the pure epoxy coil.

[0047] Conclusion: If Figure 8 and 9 As shown in the figure, through the measurement of thermal expansion coefficient and mechanical behavior, a 10wt.% zirconium tungstate / epoxy resin composite material with reduced thermal expansion coefficient, improved mechanical properties and the best comprehensive performance was selected as the improved impregnation material. After simulation verification, the radial stress of the improved impregnated coil was greatly reduced compared with the pure epoxy impregnated coil. The radial stress of the improved impregnated coil with an inner radius of r=8mm was only 4.18% of that of the pure epoxy coil, and the radial stress of the improved impregnated coil with r=6mm was only 4.31% of that of the pure epoxy coil.

Claims

1. An experimental method for a zirconium tungstate-filled epoxy resin-cured superconducting coil resistant to thermal mismatch, characterized in that: The following steps are involved: 1) Preparation of superconducting tape: Select the superconducting tape required for the experiment, and weld the current leads at both ends of the superconducting tape; arrange voltage welding points at a specified interval along the length direction of the superconducting tape, and weld silver tape leads to each voltage welding point; 2) Preparation of impregnation materials: Use Stycast@2850FT epoxy resin material and Catalyst 24LV curing agent to prepare epoxy resin matrix; the doped filler is zirconium tungstate ZrW2O8 powder with a particle size of 1μm and a purity greater than 99%; Mix epoxy resin and curing agent in proportion, stir well, add zirconium tungstate powder, stir well; use vacuum pump for vacuum degassing; 3) Coil winding: fix the winding reel of the superconducting tape prepared in step 1) on the pay-off wheel, fix the coil frame tooling on the winding machine, and use the wet winding method to impregnate the coil; Lead the superconducting tape in the winding reel to the coil frame tooling, and glue and fix the superconducting tape; evenly apply the impregnation material prepared in step 2) to the upper and lower surfaces of the superconducting tape, and start the winding machine at the same time to start winding the coil, while applying the impregnation material; during the winding process, pay attention to the silver tapes not being able to fit together, and use the impregnation material to separate them; After the winding is completed, it is subjected to constant temperature curing to obtain the required superconducting coil.

2. The experimental method of the thermal mismatch-resistant zirconium tungstate-filled epoxy resin-cured superconducting coil according to claim 1, characterized in that: In the step 1), voltage welding points are arranged on the first turn, the sixth turn, the sixteenth turn, the twenty-sixth turn, and so on of the superconducting tape, with a voltage welding point arranged every ten turns.

3. The experimental method of the thermal mismatch-resistant zirconium tungstate-filled epoxy resin-cured superconducting coil according to claim 1, characterized in that: In the step 1), the current lead is a silver tape with the specifications of 0.1 mm thickness, 3 mm width and about 10 cm length; the specifications of the silver tape on each voltage welding point are 0.1 mm thickness, 3 mm width and about 3 cm length.

4. The experimental method of the thermal mismatch-resistant zirconium tungstate-filled epoxy resin-cured superconducting coil according to claim 1, characterized in that: In the step 2), the epoxy resin material and the curing agent are mixed in a mass ratio of 100:7-10.

5. The experimental method of the thermal mismatch-resistant zirconium tungstate-filled epoxy resin-cured superconducting coil according to claim 1, characterized in that: In step 2, the added mass of the zirconium tungstate powder accounts for 9% to 11% of the sum of the mass of the epoxy resin material and the curing agent.

6. The experimental method of the thermal mismatch-resistant zirconium tungstate-filled epoxy resin-cured superconducting coil according to claim 1, characterized in that: In the step 3), the mixture is cured in a drying oven at a constant temperature of 25° C. for 24 hours.

Citation Information

Patent Citations

  • Preparation method of epoxy resin zirconium tungstate composite material

    CN102190859A

  • Second-generation high-temperature superconducting strip closed coil and preparation method thereof

    CN114220650A

  • Rare earth barium copper oxide high-temperature superconducting coil capable of avoiding delamination and manufacturing method thereof

    CN117476356A

  • Superconducting coil and superconducting device

    JP2020047739A